Crossing the paradigm of 'Including the "Self"': toward an understanding of comprehensive reflexivity and a systemic epistemology as useful concepts for social care professionals - Niall Reynolds (Scottish Journal of Residential Child Care)
Sometimes the most important relationships in a young person's life are those with the social care professionals who are charged with their care. Often these relationships develop and evolve within complex systems with an increasing move toward a culture of monetisation of care which is driven by the structures of advanced capitalism. These broader economic processes present a challenge for social care professionals in how they position themselves within often competing narratives about the delivery of care. In this paper I will discuss the concepts of adopting a systemic epistemology that encourages social care professionals to engage with themselves within the broader frame of what is called comprehensive reflexivity. Ideas will be discussed that focus on making connections between the social constructive paradigms and front line practice. It is often said of systemic psychotherapists that their area of expertise is in being non expert. They often deploy this idea deliberately in order to assess and dilute the power dynamics within relationships and employ collaborative practice techniques as a means of building meaningful relationships. The transferability of these ideas is hugely relevant to social care professionals interested in developing ethical and reflexive practice.